A consolidação da educação profissional e tecnológica e a construção da carreira do magistério do ensino básico, técnico e tecnológico - Lopes , Carina Deolinda da Silva (2024)
The work is based on the approach to the study of the career of Basic Technical and Technological Education from a historical and legal perspective, for this purpose a historical review of the legal path of education was carried out, in view of the Federal Constitutions and special legislation, as well as the trajectory that teachers who carry out their work in Professional and Technological Education have also gone through in legal and jurisprudential scope. This research seeks to highlight the legal and legal aspects of EBTT teachers, and at the same opportunity seeks to produce material that contributes to clarifying aspects related to the professional and work scope of these teachers. The theme to be presented as a research proposal intends to enable the researcher to study and better understand the theme regarding the historical and legal trajectory of the career and work of Basic, Technical and Technological Education teachers, respecting the contours that structure the EBTT teaching career in order to collaborate with the target audience of this study. The research problem of the work was to discover how the presentation and interpretation of the Basic, Technical and Technological Education (EBTT) career is carried out and what are its practical consequences in the situations that involve it? Specifically, the work initially sought to describe the historical-political scenario of professional education, study the legislation and practical and doctrinal legal content regarding the EBTT teaching career and, finally, prepare interpretative material on the topic, which adds better clarity and understanding of the federal teaching career in legal and practical terms. In structuring and research, it was verified the importance of creating material that can appeal due to the counterpoints that exist due to the teaching position in the career that teachers who work in technical and technological education find themselves in, since they can be at the head of the undergraduate and secondary education in basic education, some counterpoints are always raised between rights and responsibilities.